Facile and convenient synthesis of 2, 4-disubstituted and 2, 3, 4-trisubstituted 1, 3-thiazoles. (3rd March 2016) - Hassan, Alaa A.; Mohamed, Shaaban K.; Mohamed, Nasr K.; El-Shaieb, Kamal M.A.; Abdel-Aziz, Ahmed T.; Mague, Joel T.; Akkurt, Mehmet
ABSTRACT: An efficient route for the synthesis of ( E )-2-(2-(2-nitrobenzylidene)-hydrazinyl)-4-phenylthiazol-3-ium bromide, ( E )-2-(2(substituted benzylidene)hydrazinyl)-4-phenylthiazoles and ( E )-4-(4-bromophenyl)-2-(cycloalkylidenehydrazono)-3-phenyl-2, 3-dihydrothiazoles by reaction of 1-aryl-2-bromoethanones with 2-(1-substituted methylidene)hydrazinecarbothioamides and cycloalkylidene- N -phenyl-hydrazinecarbothioamides. The structure of the products has been confirmed by using IR, NMR, mass spectrometry and single-crystal X-ray analyses. GRAPHICAL ABSTRACT: